Cofactor requirements of BamHI mutant endonuclease E77K and its suppressor mutants. - Xu, S Y (1991)
A mutant BamHI endonuclease, E77K, belongs to a class of catalytic mutants that bind DNA efficiently but cleave DNA at a rate more than 10(3)-fold lower than that of the wild-type enzyme (S. Y. Xu and I. Schildkraut, J. Biol. Chem. 266:4425-4429, 1991). The preferred cofactor for the wild-type BamHI is Mg2+. BamHI is 10-fold less active with Mn2+ as the cofactor. In contrast, the E77K variant displays an increased activity when Mn2+ is substituted for Mg2+ in the reaction buffer. Mutations that partially suppress the E77K mutation were isolated by using an Escherichia coli indicator strain containing the dinD::lacZ fusion. These pseudorevertant endonucleases induce E. coli SOS response (as evidenced by blue colony formation) and thus presumably nick or cleave chromosomal DNA in vivo. Consistent with the in vivo result, the pseudorevertant endonucleases in the crude cell extract display site-specific partial DNA cleavage activity. DNA sequencing revealed two unique suppressing mutations that were located within two amino acid residues of the original mutation. Both pseudorevertant proteins were purified and shown to increase specific activity at least 50-fold. Like the wild-type enzyme, both pseudorevertant endonucleases prefer Mg2+ as the cofactor. Thus, the second-site mutation not only restores partial cleavage activity but also suppresses the metal preference as well. These results suggest that the Glu-77 residue may play a role in metal ion binding or in enzyme activation (allosteric transition) following sequence-specific recognition.